(untitled) - Devkota, Manish (Can Tho, 2020)
During the last couple of decade’s availability of knife fish, Notopterus notopterus in the rivers environment has been drastically declined and considered as threatened species (Haniffa et al., 2004). The present study was conducted to determine the effect of giving different hormones for ovulation and the effects of using different feed for nursing larvae were performed to understand induced breeding and larval rearing of N. notopterus in captivity. The total number of fish was 81 and the sex ratio 1:2 (male to female). The fish were given 2 mg PG as a preliminary dose and different doses of HCG (3000, 4000, 5000 IU/kg), PG (6, 8, 10 mg/kg), and LHRHa (150, 200, 250 µg/kg) as final injection with 9 treatments and 3 replicates. Larvae of knife fish were reared in 50 L tank with 3 treatments and 3 replicates up to 35 days with Moina, Tubifex worm, and commercial feed substituted in different culture days. The best dose obtained for ovulation of knife fish was 2 mg/kg PG and 200 µg/kg LHRHa with a latency period 36 hours, Ovisomatic Index Value 5.2%, egg size 3.27 mm, absolute fecundity 154-597 eggs, fertilization rate 95.2%, hatching rate 70.3% and embryo development time 159 hours. Feeding larvae with Tubifex worms during nursing found to best for growth rate and survival rate of Knife fish. The best result was obtained when larvae were fed 0-5 days Moina, 6-20 days tubifex worm, and 21-35 day feed powder with weight gain 0.31g, length gain 2.36 cm, and survival rate 59%. Therefore, it can be concluded that the optimal dose for inducing breeding of knife fish was 2 mg/kg PG + (200 µg/kg LHRHa + 20 mg DOM). Feeding larvae with Tubifex worm up to day 20 resulted in a significant difference (p<0.05) on the growth rate and survival rate of knife fish.
Keywords: Freshwater fishes,Cá nước ngọt